2011
DOI: 10.1164/rccm.201011-1813oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function and Inflammatory Responses in Healthy Young Adults Exposed to 0.06 ppm Ozone for 6.6 Hours

Abstract: Rationale: Exposure to ozone causes a decrease in spirometric lung function and an increase in airway inflammation in healthy young adults at concentrations as low as 0.08 ppm, close to the National Ambient Air Quality Standard for ground level ozone. Objectives: To test whether airway effects occur below the current ozone standard and if they are more pronounced in potentially susceptible individuals, such as those deficient in the antioxidant gene glutathione S-transferase mu 1 (GSTM1). Methods: Pulmonary fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(164 citation statements)
references
References 31 publications
4
152
1
Order By: Relevance
“…Studies since the 2005 global update have shown that healthy exercising human subjects showed impaired lung function at concentrations of 60 ppb for 6.6 h, relative to clean air controls (Kim et al, 2011). The report noted that the subjects were healthy adults and thus not representative of the general population, or of real-world combinations of susceptibility and exposure.…”
Section: Healthmentioning
confidence: 98%
“…Studies since the 2005 global update have shown that healthy exercising human subjects showed impaired lung function at concentrations of 60 ppb for 6.6 h, relative to clean air controls (Kim et al, 2011). The report noted that the subjects were healthy adults and thus not representative of the general population, or of real-world combinations of susceptibility and exposure.…”
Section: Healthmentioning
confidence: 98%
“…Schelegle et al (2009) exposed healthy young adults to varying concentrations of ozone (60, 70, 80 and 87 ppb) for 6.6 hours, with continuous exercise (V E = 40 litres per minute), and reported significant decrements at 70 ppb, but not 60 ppb. Recent studies have tended to support evidence of small, but measureable, decrements at 60 ppb (Brown, Bateson & McDonnell, 2008;Kim et al, 2011). More detailed modelling studies have provided evidence of thresholds for these transient lung function responses.…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…These data tended to suggest that the threshold of ozone-induced inflammation was somewhat higher than that for lung function changes. With respect to this question, Kim et al (2011) exposed 59 healthy, exercising young adults to 0.06 ppm ozone for 6.6 hours under controlled chamber conditions and reported a significant and acute decrease in FEV1 and increased neutrophilic inflammation of the airways, sampled using induced sputum. Of note, this paper found no influence of possession of the GSTM1 null genotype on the responses observed.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…32 Healthy human subjects exposed to 0.6-ppm O 3 , a level below the current 0.8-ppm standard, had significant O 3 -induced decreases in lung function and increased neutrophilic inflammation in the airways compared to subjects exposed to clean air. 33 Other investigators report that atopic individuals, even those without asthma, had enhanced inflammatory responses to inhaled O 3 compared to healthy subjects at O 3 levels within current NAAQS standards. 34,35 associations between clinical and subclinical manifestations of adverse pulmonary health effects and exposure to ambient air pollutants while providing some indication of potential mechanisms involved.…”
Section: Ambient Air Pollutionmentioning
confidence: 99%
“…64 Due to the central role of inflammation and oxidative stress in the response to air pollution, genes that modulate inflammation and antioxidant defense mechanisms are considered to contribute to interindividual variability in response to air pollution. 33 Genetically standardized animal models have been used to identify candidate genes that may convey an increased susceptibility to air pollution-induced health impacts on chromosomes 4, 11, and 17. These studies report correlations between several hallmarks of respiratory health effects, including lung hyperpermeability, injury and inflammation, and genetic differences within these chromosomes.…”
Section: Ambient Air Pollutionmentioning
confidence: 99%